O clima organizacional e a qualidade em serviços: um estudo de caso de um grupo de empresas de comunicação - Siqueira, Fabiana Cardoso de (2004)
This research had the main goal to verify the practices used in a interprise controled by RBS (Rede Brasil Sul de Comunicação), about the situation of the people management, to propose improvement in quality of the services realized, considering the reference through the people development, by the way of the education, qualification and training. The work of the management was realize from the particular study of a social comunication enterprises from Santa Maria (Brazil). All of sectors function in the same place and they have the administration and others departments connected. This was the first kind of study realized with all of these five organizations. The research was descriptive with analysis quantitative and qualitative. From this verification was made suggestions for the improvement of quality in services, based in keys dimension of the management proposed by Kahale (2002) and in the quality filosofy